SEDIMENT AND SUSPENDED PARTICULATE MATTER OF JAKARTA BAY, INDONESIA - Tejakusuma, Iwan G.; Adi, Seno; Nugrahadi, M.S; D., Rahmania; Yanagi, T. (Center for Environmental Technology, 2009)
Jakarta Bay is a semi enclosed bay located in the northern coast of Jakarta Metropolitan City. Hydrologically 13 rivers flowing in the Jakarta region and there are three big rivers with significant discharge to the Jakarta Bay namely Citarum, Ciliwung, and Cisadane Rivers. Jakarta, as Indonesian capital city with population of 8.725.630 inhabitants, and another 15 million people live in the surrounded suburban of Jakarta, creates a significant anthropogenic impact to the environmental system. Limited infrastructures, such as no sewerage system and lack of industrial waste management, cause the rivers in this region have over their carrying capacity.Seventeen sampling stations were determined in the Jakarta Bay, consisting of 5 stations at the river mouths (estuaries) and other 12 stations in the bay spreading from the coastal to offshore areas. Water and sediment samples were taken during 2 monsoonal or seasonal variations, August 2006 for dry season and February 2007 for rainy season respectively. Additionally, samples were also taken in May 2007.Sediment distribution in the estuary consists mostly of black clay. The sediments clays were bad smell. In the coastal region and in the dry season, the sediments consists of black clay and at one sampling site (station S3) the sediment was bad smell. However, all sampling sites became bad smell in the rainy season. In the inner bay area, sediments were greyish green sandy clay with some shell fragments. In the outer bay, the sediments were dominated by greyish green clayey sand with some shell fragments. The black clay with bad smell is indicative of anthropogenic influence from Jakarta River Basin. C/N ratio of the sediments in the dry season ranged from 1 to about 4.2 where in the estuaries (at stations M1, M2 and M4) the ratio were higher compared to the inner and outer bays. The C/N ratio of suspended particulate matter ranged from the lowest ratio of 0.7 to the highest ratio of 17.7 at the bottom layer and lesser ranged of 0.7 to 9.8 at Ã‚Â surface layer. POC concentrations ranged between 50-650 Ã‚ÂµM and 50-900 Ã‚ÂµM, in February and May, respectively. High concentrations of POC exists along the coastline or estuaries then decreasing toward the sea. POC is distributed widely in February than that in May due to higher discharge from the rivers. The average TOC concentrations in February is lower than that in May, but the TOC load in February was much higher than that in May due to the big differences of river discharge and because the samples were taken a week after the big flood in Jakarta area (February 4th - 6th, 2007). Total organic carbon fluxes from the river to the bay in February and May 2007 were 107.6 T /day C and 42.7 T /day C, respectively.Ã‚Â Key words : sediment, anthropogenic influence, C/N Ratio, POC, TOC, flux